Shipbuilding on Prince Edward Island : Entreprise in a Maritime setting, 1787-1920 - De Jong, Nicolas J., 1943- (Book collections on Project MUSE., 1994)
"Between the late eighteenth and mid-nineteenth century, Prince Edward Islanders became some of the most productive shipbuilders in the world, thereby transforming their provincial economy. This detailed examination of wooden shipbuilding on the island traces the industry's cycles of prosperity and decline and describes the types of vessels built, production profiles and market orientation. Accounts of shipbuilding at the community level reveal the local impact of financing and constructing vessels and document how the industry facilitated the distribution of timber and agricultural surpluses. Amply illustrated, this is a major contribution to Island history."--Jacket